Decision models for earthmoving techniques - Pradhan, Niranjan Man; Techapun Raengkhum; Kirby, E.S.; Sharif, M. N.; Government of Canada (Bangkok : Asian Institute of Technology, 1976)
This research study is concerned with the earthmoving operation and earthmoving techniques in construction as general. The aim of this study is to provide decision makers of the developing countries with a set of methodological tools to assess the productivity and cost of earthmoving equipments and labour, and to determine the optimum combination of earthmoving resources in any conditions. Mathematical Models are formulated to compute t he productivity and cost of equipments and labour in different circumstances along with hypothetical examples and discussions on the parameters which influence the above factors. With the discussions of appropriate technology for developing countries in earthmoving operation, a Linear Programming Model is formulated to find the optimum combination of earthmoving resources. Examples are also given to illustrate t he Model along with a sensitivity analysis. To satisfy the multiple objectives in earthmoving operations, a Goal Programming Model is formulated with some examples. And at the end Recommendations for future work are suggested.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1976
Keywords: Earthmoving machinery; Decision-making